The role of monitoring and evaluation in promoting good governance in South Africa: a case study of the Department of Social Development - Naidoo, Indrakumaran Arumugam (My University, 2012)
This thesis set out to examine the role played by monitoring and evaluation (M&E) in promoting good governance in South Africa. It examined how M&E, in promoting democratic and good governance deliverables, such as transparency, accountability and learning, influences public administration practice. The reciprocity between democracy and M&E was demonstrated by assessing how the country managed democratic transition, the influence of globalisation on country practice, and specifically how the developmental State advances good governance. The thesis reviewed the evolution of M&E at the continental and country level, and also examined how the discipline has evolved over time, and its particular application in South Africa. A comprehensive overview of the oversight infrastructure was conducted, and tested against the performance of the Department of Social Development (DSD), the case study. Through an assessment of three distinct, but interrelated M&E perspectives, termed mandatory, persuasive and civic M&E, a differentiated picture of policy and actual performance was seen. It was found that mandatory M&E was strong, and the DSD generally performed well against this benchmark. Mandatory M&E also provided the legal basis and support for other forms of M&E. However, it was not always clear that compliance on its own leads to good governance. In examining persuasive M&E, the decision-making environment within the DSD was assessed, and the role of the DSD M&E function examined in terms of, amongst others, improving learning. Civic M&E revealed that the DSD has considered and acted upon the results of the non-government sector in revising its policies. However, there was no effective civic M&E at community level, largely due to uncoordinated or weak NGOs, many of whom were now contracted to the DSD. The research suggests that whilst information has been generated through different forms of M&E, without effective follow-through by decision-makers, it generated transparency, and not necessarily accountability. Furthermore, administrative compliance cannot on its own tantamount to good governance. The thesis argues for methodological pluralism, stronger civic M&E, and confirms the assertion that M&E promotes good governance.
Keywords: Public Administration; South Africa; Transparency; Accountability